‘Austerity in the City. Crisis and Resilience in Local Context: The Case of Lisbon’ - Accornero, G. (23rd International Conference of Europeanists, 2016)
The application of the austerity measures imposed by the memorandum of understanding (MoU) signed in 2011 between the Portuguese government and the so-called ‘Troika’ had profound repercussions at a social and economic level throughout the entire country. However, the city of Lisbon was the place where these measures had the most serious effects, as it was here that unemployment, social inequalities, emigration and default on loans increased more than anywhere else in Portugal. The pressure exerted towards greater administrative centralisation derived from the MoU also led to severe cuts in local public expenditure, which contributed to worsening this situation. Accordingly, Lisbon was the principal scenario, from 2011 through to 2013, of a strong wave of anti-austerity protests. At the same time, policies aimed at mitigating the social impacts of the crisis and austerity – ‘anti-cycle’ policies – were implemented by Lisbon city council, countering the trend followed by the central government’s policy. In part, institutional allies of the contentious actors emerging in the context of crisis, they were above all advocates of the civic list ‘Citizens for Lisbon’, the guide to the council department for housing and local development and the council department for social rights, pursuing the implementation of these policies. Based on these premises, this study aims to analyse how the instances of the social movements and new institutional actors, that emerged in this context of crisis, were interlinked and contributed to the specific response given by the city of Lisbon to the crisis and austerity.